Dropout and Persistence in Adult Basic Education - Clark, Lisa K. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
A review of research on dropouts from adult basic education (ABE) reveals several theoretical models relevant to the study of dropout and persistence in ABE, shows specific variables related to dropout behavior, provides insights as to who drops out and why, identifies some characteristics of disadvantaged adult learners, and reveals some problems with existing ABE programs. However, a great deal of research on dropouts and persistence in ABE has focused on classifying who is dropout prone, particularly in terms of sociodemographic attributes, but has failed to probe the reasons why learners drop out or to address how dropout can be prevented. The tendency to minimize the significance of situational variables and to view them as simply beyond the control of ABE programs seems to reflect the belief that high dropout rates must stem from the failure of students rather than weaknesses in program structure or services. Very little research has attempted to illuminate the relationship between instructional strategies and dropout/persistence in ABE. For the most part, research on dropout and persistence in ABE has attempted to examine specific variables in isolation, often ignoring the interaction of a given factor with other related factors. Finally, it appears that conclusions about dropout behavior are usually based on the opinions of teachers and administrators but rarely consider the perspectives of ABE students. (KC)
ERIC Note: Master's thesis, North Carolina State University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Persistence; Adult Basic Education; Disadvantaged; Dropout Characteristics; Dropout Prevention; Dropout Research; Dropouts; Program Improvement; Research Methodology; Research Problems; Student Characteristics; Dissertations/Theses, Masters Theses; Information Analyses